Polymorphism of the Pfcrt Gene and Epidemiological Characteristics in Patients with Uncomplicated Malaria at the CSU-COM Hospital of Riviera Palmeraie (Abidjan) - Bla, Kouakou Brice; Bognini, Akou Sara Adélaïde; Kouakou, Aby Jerome; Konaté-Touré, Abibatou; Mensah-Akaki, Juliana; Gnagne, Akpa Paterne; Djaman, Allico Joseph; Yavo, William (European Journal of Applied Sciences, 2022)
Although recent data has shown a reduction by halve of malaria-related deaths, over the last three years controlling or even eliminating malaria remains a real challenge. In 2004, the high prevalence of isolates carrying the pcfrt-76T mutant allele led to the discontinuation of the use of chloroquine (CQ) as an antimalarial. Several years after its withdrawal, there is growing talk of a re-emergence of CQ sensitivity. The aim of this study was to monitor alleles of the pfcrt gene, a molecular marker of CQ resistance (CQ-R). A descriptive prospective study was conducted from September to August 2020 at the Community Health Center of Riviera Palmeraie, Abidjan (CSU-COM). One hundred and twenty (120) blood samples were collected from patients with uncomplicated P. falciparum malaria, dried on Whatman 3MM paper for 48 hours at laboratory temperature. After DNA extraction with Chelex® 100, nested PCR and enzymatic digestion with Apo I were used to demonstrate the restriction polymorphism of the pfcrt gene at codon 76. A prevalence of 16% was observed for the mutant pfcrt-76T allele, responsible for chloroquine resistance, compared with 84% for the wild-type pfcrt-K76 allele. This study highlighted a decrease in Plasmodium falciparum isolates carrying the chloroquine resistance allele, thus confirming previous data on CQ-R in Côte d'Ivoire.